IDENTIFICATION OF THE MAIN RISK FACTORS AMONG PATIENTS WITH CIRCULATORY DISEASES (World Bulletin of Public Health, 2022)
CVDs are largely preventable by population-wide interventions and improved access to individual health care, which can significantly reduce the health burden as well as the socioeconomic burden of these diseases and their risk factors
Keywords: Circulatory system diseases; risk factor; disease burden; lifestyle